KEPATUHAN PERAWAT MELAKSANAKAN PRINSIP DUA BELAS BENAR PEMBERIAN OBAT - Yuliati, Ignata; Setyawati, Emiliana Indah Eko; Wahyuni, Sri (Sekolah Tinggi Ilmu Kesehatan Katolik St. Vincentius a Paulo Surabaya, 2022)
The behavior of nurses in giving drugs to patients must be in accordance with Standard Operational Procedures (SPO) so that patients are safe from drug-administration errors. There is still a lack of knowledge of nurses about the 12 correct principles of giving drugs to patients, not double checking with other nurses when giving drugs and there are still nurses who do not wait for patients to take their drugs and leave drugs on the patient's table. This study aims to identify the compliance of nurses in implementing the 12 correct principles of drug administration. This research design uses a descriptive study. The number of samples was 40 implementing nurses who were selected using simple random sampling. The measuring instrument used is a knowledge and compliance questionnaire of nurses about the twelve correct principles of drug administration. Data were analyzed using Descriptive Statistical Proportion Percentage Analysis (ASDPP). The results showed that most of the more than 50% (65%) of the respondents had an obedient attitude. Nurses more often do double checks before giving drugs. The Head of the Division of Nursing can provide updates on the 12 correct principles of drug administration.